An unusual case of solitary metachronous calf metastasis from gastric carcinoma after curative surgery - Mukherjee, Priyanka; Barik, Sandip Kumar; Purkait, Suvendu; Ahmed, S K Soel; Das, Deepak Kumar; Majumdar, Saroj Kumar Das; Parida, Dillip Kumar (Indian Journal of Case Reports, 2024)
Gastric carcinoma is the fifth most common cancer worldwide and a significant cause of cancer-related mortality. It commonly metastasizes to the liver, peritoneum, lungs, and bones. We highlight a rare case with solitary metachronous metastasis to the soleus muscle. A 70-year-old man was evaluated for complaints of dysphagia and diagnosed with locally advanced gastric carcinoma. He underwent radical gastrectomy followed by adjuvant chemotherapy and remained disease free for 2.5 years. Subsequently, he developed a painless swelling in the right calf. Radiological and functional imaging showed an intramuscular lesion within the right soleus muscle with no evidence of disease elsewhere. Histopathological examination of the swelling revealed metastatic adenocarcinoma, consistent with gastric primary. He was started on palliative chemotherapy. Solitary skeletal muscle metastasis with a well-controlled primary is challenging to diagnose and requires histopathology and immunohistochemistry to differentiate it from other soft-tissue neoplasms. The prognosis is poor and the intent of treatment remains palliative.